2014
DOI: 10.1007/s00261-014-0129-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sporadic renal angiomyolipoma: a retrospective analysis of 61,389 in- and out-patients

Abstract: The analysis of 61,389 patients revealed a higher prevalence of sporadic angiomyolipoma than previously observed in smaller studies. There was a significantly higher prevalence in females than in males. Multiple and bilateral angiomyolipomas were rare, and tumor growth was marginal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 26 publications
0
71
1
5
Order By: Relevance
“…The authors found an overall prevalence of 0.44%, predominated by females (68%), 57% of cases involved the right kidney, 61% cases were followed over a mean period of 25 months and showed no significant increase in tumor size during the period of follow up. 12 Predominance in females could be explained by the possible involvement of female hormones in the initiation and progression of tumor genesis. 3,5,13 Moreover, greater risk of tumor rupture and bleeding has been established during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found an overall prevalence of 0.44%, predominated by females (68%), 57% of cases involved the right kidney, 61% cases were followed over a mean period of 25 months and showed no significant increase in tumor size during the period of follow up. 12 Predominance in females could be explained by the possible involvement of female hormones in the initiation and progression of tumor genesis. 3,5,13 Moreover, greater risk of tumor rupture and bleeding has been established during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the infrequent occurrence of bilateral involvement in sporadic AML (1.5% of sporadic cases), this feature raises the clinical suspicion for TS [Fittschen et al, 2014]. The only unusual phenotype in our adult patient was the development of bilateral renal AML.…”
Section: Discussionmentioning
confidence: 83%
“…A leggyakoribb típusok az angiomyolipoma (AML), az adenoma és az oncocytoma. A fenti csoportból az AML-lel találkozunk legtöbbször, jellegzetesen középkorú nők [12] és sclerosis tuberosá-ban szenvedő gyermekek között [13]. A daganat rendellenes erekből, simaizomsejtekből és zsírból, illetve ezek különböző arányú keverékéből áll.…”
Section: áLtalános Megfontolásokunclassified